El Otro Lado de la Rosa - Pineda Cortes, Daniel Hernando (Universidad Antonio Nariño, 2023)
The Other Side of the Rose is a creation project in plastic and visual arts. It presents an installation made up of photographic images and some objects that allude to the recognition of an identity in transformation.